2015
DOI: 10.1109/tasc.2014.2361933
|View full text |Cite
|
Sign up to set email alerts
|

Accelerator-Quality HTS Dipole Magnet Demonstrator Designs for the EuCARD-2 5-T 40-mm Clear Aperture Magnet

Abstract: Future high-energy accelerators will need very high magnetic fields in the range of 20 T. The EuCARD-2 work-package-10 is a collaborative push to take HTS materials into an accelerator quality demonstrator magnet. The demonstrator will produce 5 T standalone and between 17 T and 20 T, when inserted into the 100 mm aperture of Fresca-2 high field out-sert magnet. The HTS magnet will demonstrate the field strength and field quality that can be achieved. An effective quench detection and protection system will ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 12 publications
(14 reference statements)
1
67
0
Order By: Relevance
“…This work consists of modelling the Feather-M2 aligned block coil, the main deliverable of EuCARD-2-WP10 program (see [2]). The coil is an 800 mm long race track dipole, where each pole is composed of a two-layer coil (see Fig.…”
Section: A Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…This work consists of modelling the Feather-M2 aligned block coil, the main deliverable of EuCARD-2-WP10 program (see [2]). The coil is an 800 mm long race track dipole, where each pole is composed of a two-layer coil (see Fig.…”
Section: A Generalmentioning
confidence: 99%
“…T HIS paper presents a new type of modelling of the HTS magnets utilizing Finite Element Analysis (FEA) and presents the relevant steps in the modelling process of impregnated coils wound with Roebel cable for accelerator magnets of the program EuCARD-2 ([1], [2], [3], [4], [5]). Usually, the coils of the LTS magnets have been modelled as block domain coil pack utilizing anisotropic material properties for the central cross-section of the coil [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…A cable width of 12 mm is a good compromise for magnet designs based either on the classical blocks or cos-theta configurations [56]. This is the initial width of the tape, which is cut in meanders with a residual tape width of 5.5 mm and a periodicity of 226 mm (based on existing tooling).…”
Section: G Cable Designmentioning
confidence: 99%
“…Progress about the EuCARD-WP7 HFS racetrack insert can be found in [5]. As for the EuCARD2 project, it focuses on a ten kA-class HTS cable and on a dipole insert for which various coil configurations have been investigated: block design with stack tapes [6], or with Roebel cable [7] -currently under construction [8] -as well as cosθ insert design made of Roebel cable. This paper is a follow-up of the latter for which previous work has showed that a classical double-layer configuration of the cosθ insert would lead to non-bearable stress in the winding [9].…”
Section: Index Terms-superconducting Dipole Magnet Hts Roebel Cablementioning
confidence: 99%